Neutrophil extracellular traps impede cancer metastatic seeding via protease-activated receptor 2-mediated downregulation of phagocytic checkpoint CD24 - Yu Liu; Xiaoli Zhang; Kun Chen; Hongying Wang; Junhu Yuan; Yiming Ma; Jianhui Ma; Fanyu Zhang; Bing-zhi Wang; Yinong Wang; Xinhua Zhao (Journal for ImmunoTherapy of Cancer)
Background Phagocytic clearance by macrophages represents a critical immune surveillance mechanism in cancer liver metastasis. Neutrophils, the most abundant immune cells encountered by cancer cells in circulation, play key roles in metastasis through neutrophil extracellular traps (NETs). Although NETs promote macrophage phagocytosis during infection, whether they regulate phagocytosis during cancer metastasis is unknown. The present study aimed to explore the roles of NETs in regulating macrophage phagocytosis during the seeding process of liver metastasis and the mechanisms underlying the roles.Methods A lipopolysaccharide-induced NET model was applied to study the role of NETs on colorectal cancer (CRC) liver metastasis. The neutrophils isolated from human peripheral blood were stimulated with PMA to release NETs, which were collected and added to the cultures of different CRC cell lines for in vitro studies. Macrophage phagocytosis was assessed with flow cytometry in vitro and in vivo. RNA-seq and microRNA array analyses were performed to identify key pathways regulated by NETs and downstream key molecules. The macrophage phenotypes were evaluated using immunohistochemistry, flow cytometry, and cytokine and chemokine arrays.Results NETs promote macrophage phagocytosis both in vitro and in vivo. Neutrophil elastase (NE), which was able to inactivate the canonical signal of protease-activated receptor 2 (PAR2), downregulated the phagocytotic checkpoint CD24. Notably, PAR2 deficiency imitated the effect of NETs on phagocytosis and CD24. Mechanistic studies indicated that inhibiting PAR2 expression upregulated miR-34a and miR-146a and downregulated CD24 in cancer cells. In addition, PAR2 depletion enhanced the recruitment and M1 polarization of macrophages by upregulating CSF-1 and CXCL1. The correlation of NETs/NE and CD24 was corroborated using human CRC specimens. Furthermore, PAR2 blockade combined with an anti-EGFR antibody (cetuximab (CTX)) synergistically enhanced the phagocytic ability of macrophages and suppressed liver metastasis in vivo.Conclusions NET-derived elastase inactivated PAR2 canonical signaling and promoted phagocytosis by downregulating CD24, which functions as a phagocytotic checkpoint in CRC liver metastasis. Thus, PAR2 inhibitors combined with CTX may serve as a novel therapeutic strategy against advanced CRC.